Application of Cooperative Distributed Predictive Control in Power Grid Frequency Adjustment - Iranmanesh, Hamidreza; Afshar, Ahmad (Ciência e Natura, 2015)
One of the efficient control methods is the model predictive control(MPC) that calculates appropriate system inputs to reduce the difference between the desired and the system predicted output. One of the important applications of this strategy is in power grids for load-frequency control and power balancing. Different architectures of MPC are applied in large scale structures such as power grid. In this paper a feasible cooperation based MPC(FC-MPC) controller has been used as a suited solution to control problem with relatively strict constraints. Also it can be used as one of options for control system of smart grids in future. In this paper, a power grid with 4 control zones has been chosen as a case study. The simulation results indicate the superior performance of the discussed control method in comparison with the traditional control of load- frequency.